Pentoxifylline for Anemia in Chronic Kidney Disease: A Systematic Review and Meta-Analysis. - Davide Bolignano; Graziella D'Arrigo; Anna Pisano; Giuseppe Coppolino (PLoS ONE)
Background Pentoxifylline (PTX) is a promising therapeutic approach for reducing inflammation and improving anemia associated to various systemic disorders. However, whether this agent may be helpful for anemia management also in CKD patients is still object of debate. Study design Systematic review and meta-analysis. Population Adults with CKD (any KDOQI stage, including ESKD patients on regular dialysis) and anemia (Hb<13 g/dL in men or < 12 g/dL in women). Search strategy and sources Cochrane CENTRAL, EMBASE, Ovid-MEDLINE and PubMed were searched for studies providing data on the effects of PTX on anemia parameters in CKD patients without design or follow-up restriction. Intervention PTX derivatives at any dose regimen. Outcomes Hemoglobin, hematocrit, ESAs dosage and resistance (ERI), iron indexes (ferritin, serum iron, TIBC, transferrin and serum hepcidin) and adverse events. Results We retrieved 11 studies (377 patients) including seven randomized controlled trials (all comparing PTX to placebo or standard therapy) one retrospective case-control study and three prospective uncontrolled studies. Overall, PTX increased hemoglobin in three uncontrolled studies but such improvement was not confirmed in a meta-analysis of seven studies (299 patients) (MD 0.12 g/dL, 95% CI -0.22 to 0.47). Similarly, there were no conclusive effects of PTX on hematocrit, ESAs dose, ferritin and TSAT in pooled analyses. Data on serum iron, ERI, TIBC and hepcidin were based on single studies. No evidence of increased rate of adverse events was also noticed. Limitations Small sample size and limited number of studies. High heterogeneity among studies with respect to CKD and anemia severity, duration of intervention and responsiveness/current therapy with iron or ESAs. Conclusions There is currently no conclusive evidence supporting the utility of pentoxifylline for improving anemia control in CKD patients. Future trials designed on hard, patient-centered outcomes with larger sample size and longer follow-up are advocated.